Occupied economies : an economic history of Nazi-occupied Europe, 1939-1945 /: an economic history of Nazi-occupied Europe, 1939-1945. (2012) - Klemann, Hein A. M, 1957-; Kudryashov, Sergei; Etmektsoglou, Gabriella; Lund, Joachim, 1967-; Terry, N (Nick)
No abstract available